OUTCOMES OF LOWER LIMB REHABILITATION USING THE ROBOTIC GAIT TRAINING SYSTEM IN STROKE PATIENTS (Vietnam Journal of Community Medicine, 2026)
Background:Stroke is a leading cause of mortality and long-term disability in adults, in which recovery of walking ability plays a crucial role for patients with lower-limb paralysis. Recently, the GTR-A adaptive robotic gait training system has been implemented at the Rehabilitation Center of Bach Mai Hospital; however, its clinical effectiveness in Vietnam has not been fully evaluated. This study aimed to assess the effectiveness of lower-limb rehabilitation in stroke patients using the GTR-A system.Methods:A prospective, non-controlled interventional study with a pre–post design and a comparative analysis between two intervention groups was conducted on 32 patients with post-stroke hemiplegia and a Functional Ambulation Category (FAC) score ≥2. Patients were randomly assigned to either a Passive training group or an Active-Assisted training group. The robotic gait training program using the GTR-A system was performed three sessions per week for one month. Outcome measures included heart rate parameters, FAC, Berg Balance Scale (BBS), Timed Up and Go test (TUG), and patient satisfaction.Results:After the intervention, both groups showed statistically significant improvements in most outcome measures (p
Keywords: Stroke; GTR-A robot; rehabilitation; lower limbs; gait training.